Risco de Farmingham e evento cardiovascular em mulheres com síndrome dos ovários policísticos - Santos, Ana Gabriela Pontes [UNESP] (2014)
Introduction: Women with polycystic ovary syndrome (PCOS) have an increased prevalence of cardiovascular risk factors. However, most studies available are limited to confirming the association of PCOS with cardiovascular morbidity and mortality. Objectives: To assess the Framingham risk score and the prevalence of cardiovascular events in women with PCOS. Patients and Methods: Clinical, biochemical and ultrasonographic data were collected from women (18-40 years) with and without PCOS attending the Botucatu Medical School Hospital from 1997 to 2010. The Framingham Risk Score (FRS), calculated according to NCEP-ATPIII-2002 criteria, was used to estimate the 10-year risk of first coronary event. The prevalence of major and minor cardiovascular events was obtained through the analysis of medical records, crossing of data, and active search. Statistical analyses were performed using the Chi-square test, Fischer’s exact test and multiple logistic regression adjusted for age and BMI, with significance set at 5%. Results:t A total of 267 women with PCOS and 190 without PCOS were followed up for 1-13 years. Median age was 25 years in women with PCOS, and 29.5 yearsnin those without it (p<0.0001). Women with PCOS had higher prevalence of obesity (p=0.017), waist circumference (p= 0.012), arterial hypertension (p=0.047), glucose intolerance (p=0.027), type 2 diabetes mellitus (p=0.007 hypercholesterolemia (p=0.005), and hypertriglyceridemia (0.002) than those without PCOS. The prevalence of high FRS was 7.5% and 1.3% in women with and without PCOS, respectively (p=0.008). Multiple logistic regression analysis revealed that women with PCOS had a 5-fold greater chance of having a coronary event than those without PCOS (OR: 5.16 95%CI:1.16-22.96, p=0.031). However, the prevalence of cardiovascular events did not statistically differ between women with and without PCOS. Conclusions: In the women with PCOS at childbearing age who participated in this ...